Gender performances on social media: A comparative study of three top key opinion leaders in China - Liu, Ming; Zhao, Ruinan; Feng, Jieyun (Frontiers in Psychology, 2022)
This study gives a critical examination of the performances of three top KOLs on social media in China to explore whether gender serves as an important social factor in their interaction with their followers. A critical analysis of their Weibo posts has revealed that they construct different gender identities through their preferential choices of personality traits, speech acts, and addressing terms. This can be explained in terms of their target consumers and the products they promote. It concludes that although gender can serve as an important factor in top KOLs’ performances on social media, it can be appropriated and exploited in varied ways to serve different communicative purposes.